Effect of Spiritual Leadership and Job Satisfaction on Organizational Citizenship Behavior in Generation Y Employees: The Mediating Role of Spirituality in the Workplace - Puspitasari, Diva Dwi; Maksum, Ikhsan (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to examine the influence of spiritual leadership and job satisfaction on Organizational Citizenship Behavior and spirituality at work as a mediating variable in millennial employees at an electronic assembly company in Batam. Methodology: This research uses a quantitative approach with a sample of 261 employees and data analysis is carried out statistically to test the relationship between variables. Results: This study shows that spiritual leadership has no significant effect on OCB (T-Statistics 1.059, P-Value 0.290). In contrast, job satisfaction had a positive and significant effect on OCB (T-Statistics 4.090, P-Value 0.000). Spirituality at work did not mediate the effect of spiritual leadership on OCB, but did significantly mediate the relationship between job satisfaction and OCB. Findings: Job satisfaction influenced OCB more than spiritual leadership, with workplace spirituality mediating the relationship and driving employee motivation. Novelty: The study found that spiritual leadership indirectly influenced OCB, but job satisfaction was a significant mediator, particularly among millennial employees in the electronics manufacturing industry. Originality: This study highlights that spiritual leadership indirectly affects OCB, but job satisfaction is a significant mediator, offering a new perspective on the importance of focusing on job satisfaction among millennial employees in the electronics manufacturing industry. Conclusion: The study concluded that spiritual leadership does not directly influence OCB, but job satisfaction is a significant mediator. Organizations need to improve job satisfaction to encourage OCB among millennial employees. Type of Paper: This type of article is a research article that presents empirical findings on the effect of spiritual leadership on Organizational Citizenship Behavior (OCB) with a focus on the role of job satisfaction as a mediator.Â